Design of a randomized clinical trial of a colorectal cancer screening decision aid to promote appropriate screening in community-dwelling older adults. (December 2017) - Kistler, Christine E; Golin, Carol; Morris, Carolyn; Dalton, Alexandra F; Harris, Russell P; Dolor, Rowena; Ferrari, Renée M; Brewer, Noel T; Lewis, Carmen L
Background: Appropriate colorectal cancer screening in older adults should be aligned with the likelihood of net benefit. In general, patient decision aids improve knowledge and values clarity, but in older adults, they may also help patients identify their individual likelihood of benefit and foster individualized decision-making. We report on the design of a randomized clinical trial to understand the effects of a patient decision aid on appropriate colorectal cancer screening. This report includes a description of the baseline characteristics of participants. Methods: English-speaking primary care patients aged 70–84 years who were not currently up to date with screening were recruited into a randomized clinical trial comparing a tailored colorectal cancer screening decision aid with an attention control. The intervention group received a decision aid that included a values clarification exercise and individualized decision-making worksheet, while the control group received an educational pamphlet on safe driving behaviors. The primary outcome was appropriate screening at 6 months based on chart review. We used a composite measure to define appropriate screening as screening for participants in good health, a discussion about screening for patients in intermediate health, and no screening for patients in poor health. Health state was objectively determined using patients' Charlson Comorbidity Index score and age. Results: A total of 14 practices in central North Carolina participated as part of a practice-based research network. In total, 424 patients were recruited to participate and completed a baseline visit. Overall, 79% of participants were White and 58% female, with a mean age of 76.8 years. Patient characteristics between groups were similar by age, gender, race, education, insurance coverage, or work status. Overall, 70% had some college education or more, 57% were married, and virtually all had Medicare insurance (90%). The three primary medical conditions among the cohort were a history of diabetes, pneumonia, and cancer (28%, 26%, and 21%, respectively). Conclusion: We designed a randomized clinical trial to test a novel use of a patient decision aid to promote appropriate colorectal cancer screening and have recruited a diverse study population that seems similar between the intervention and control groups. The study should be able to determine the ability of a patient decision aid to increase individualized and appropriate colorectal cancer screening.